Application of low modulus polymeric fibers in engineered cementitious composites. (April 2014) - Halvaei, Mana; Jamshidi, Masoud; Latifi, Masoud
Nowadays, the advantages of staple fibers applied as reinforcement in cementitious composites are well known. The fiber to cement interfacial interactions influences mechanical properties of composites. Engineered cementitious composites are cement-based composites which are made of cement binder, small size sands, fillers, high modulus fibers, and supplementary cementing materials. They have improved tensile and flexural properties in comparison to normal concretes. To achieve these properties, high modulus fibers such as carbon, steel, and polyvinyl alcohol fibers have been used in engineered cementitious composites. In this research, low modulus polymeric fibers such as nylon 66, acrylic, and polypropylene were used as substitute of high modulus reinforcing fibers in engineered cementitious composite. The low modulus fibers were characterized carefully for physical–mechanical properties. The flexural behavior (flexural strength and flexural toughness) of the engineered cementitious composite specimens from this article was studied using a three-point bending test method. The results were compared to engineered cementitious composite containing polyvinyl alcohol. It was found that low modulus fibers caused considerable improvement in flexural behavior but results were lower than composites containing polyvinyl alcohol fiber. It was also found that these fibers are suitable choices for producing low price, acceptable performance engineered cementitious composites for usual applications in construction industry.